An Analysis of the Effects of Cigarette Addiction among Adolescents in Simpang Village, Seluma Regency - Wati, Ledia Aprelia; Puspitasari, Rini; Yunarman, Sepri; Fitriana, Rossi Delta (The Future of Education Journal, 2026)
This study analyzes the causes and impacts of cigarette addiction among adolescents in Simpang Village, Seluma Regency. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews with eight informants (adolescents, parents, and village officials), and documentation studies. The findings identified three main factors contributing to cigarette addiction: internal factors (curiosity and the search for comfort), peer influence (the most dominant factor), and a permissive social environment with easy access to single-stick cigarettes sold at affordable prices starting from IDR 1,000 per stick. Adolescents generally begin smoking between the ages of 14 and 15. The impacts of cigarette addiction are multidimensional, covering health, psychological, social, educational, and economic aspects, with the prevalence of adolescent smokers in the village reaching approximately 80%. The study concludes that adolescent smoking behavior in Simpang Village has developed into a systemic issue that requires integrated interventions from various stakeholders, including families, schools, village governments, and local health institutions.